2018
DOI: 10.1016/j.jspr.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative oxygen consumption during development of two postharvest insect pests: Callosobruchus maculatus Fabricius and Plodia interpunctella Hübner

Abstract: Insect pests such as Callosobruchus maculatus Fabricius and Plodia interpunctella Hübner cause substantial losses to grain during postharvest storage. In the last few years, hermetic storage technologies have been successfully used by smallholder farmers in Africa and Asia to protect their harvested grain against insect pests. Hermetic technologies owe much of their effectiveness to restricting oxygen availability to insects confined in the containers. There is a need to better understand the biology of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Other studies have assessed the individual insect consumption rates at normoxic conditions and found that approximately 8 mL O 2 is needed during the lifetime of C. maculatus adults (egg to adult emergence) [ 14 , 42 , 43 ]. Our findings focused on adult stages under hypoxic conditions which prompted the insects to reduce their metabolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have assessed the individual insect consumption rates at normoxic conditions and found that approximately 8 mL O 2 is needed during the lifetime of C. maculatus adults (egg to adult emergence) [ 14 , 42 , 43 ]. Our findings focused on adult stages under hypoxic conditions which prompted the insects to reduce their metabolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Even though survivors can continue their development and reproduction after a sublethal exposure, our study found that they performed poorly as a function of either delayed development, increased mortality, or reduced oviposition. The average life cycle of P. interpunctella (from egg to adult emergence) at 25°C and 40% RH was 7 days under hermetic condition (Quellhorst et al ., 2018). The pupation rate and emergence rate of the P. interpunctella larvae (20 days after egg hatching) in 5% O 2 were 85 and 11%, respectively, while they were 100% in the control.…”
Section: Discussionmentioning
confidence: 99%
“…This bag is a common packaging material for sesame staying stored for about a year in Ethiopia and Sudan. On the other hand, (Odjo et al 2020;Ndegwa et al 2016;Quellhorst et al 2018;Tefera et al 2011) reported that hermetic technologies like Perdue Improved Crop Storage (PICS) bags are crucial in reducing postharvest losses in many crops. The PICS bag is relatively better than polypropylene (pp) bags, sisal sacks and polyethylene lined polypropylene bags for sesame storage with germination rate of 93% after stored for 12 months (HuARC 2019).…”
Section: Storage Conditions and Storage Duration Storage Conditions A...mentioning
confidence: 99%